2014
DOI: 10.1155/2014/451065
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Unique Structural and Functional Properties of Malarial Glycolytic Enzymes for Antimalarial Drug Development

Abstract: Metabolic enzymes have been known to carry out a variety of functions besides their normal housekeeping roles known as “moonlighting functions.” These functionalities arise from structural changes induced by posttranslational modifications and/or binding of interacting proteins. Glycolysis is the sole source of energy generation for malaria parasite Plasmodium falciparum, hence a potential pathway for therapeutic intervention. Crystal structures of several P. falciparum glycolytic enzymes have been solved, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…In addition, glycolysis inhibitors deplete parasite ATP (van Schalkwyk et al, 2008). Taken together, these results strongly indicate that glycolysis is vital for parasite growth and thus components of the glycolytic pathway should be considered as promising targets for novel therapeutics (Alam et al, 2014;Preuss et al, 2012). Consistent with this hypothesis, many glucose analogs have been shown to have antiparasitic activity (Santos de Macedo et al, 2001;Udeinya & Van Dyke, 1981;van Schalkwyk et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, glycolysis inhibitors deplete parasite ATP (van Schalkwyk et al, 2008). Taken together, these results strongly indicate that glycolysis is vital for parasite growth and thus components of the glycolytic pathway should be considered as promising targets for novel therapeutics (Alam et al, 2014;Preuss et al, 2012). Consistent with this hypothesis, many glucose analogs have been shown to have antiparasitic activity (Santos de Macedo et al, 2001;Udeinya & Van Dyke, 1981;van Schalkwyk et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…Only a single class of drug (8-aminoquinolines), the mode of action of which is not well understood, is active against hypnozoites, and its use is complicated and potentially lethal to the patient (Wells et al, 2010). During the intra-erythrocytic stage of the parasite, which causes pathogenesis in humans, glucose metabolism via glycolysis plays a critical metabolic role for the parasite (Alam et al, 2014;Preuss et al, 2012;Vaidya & Mather, 2009). Glucose consumption is up to 100-fold higher in erythrocytes infected with parasites (Roth et al, 1982) and knockout of the parasite glucose transporter appears to be lethal (Slavic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the substrate specificity loop (residues 97-112) has a penta peptide insertion (Bzik et al 1993) that forms a separate cavity in the surface adjacent to the catalytic region which is absent in mammalian LDHs (Dunn et al 1996). These structural differences could be exploited for selective targeting of the parasite enzyme (Alam et al 2014). Based on the previous investigations of Plasmodium species (Cameron et al 2004, Dunn et al 1996, we aimed to inquire the possibility of designing new anti-theilerial drugs from the data on TpLDH in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Enolase was found in MPs of 38 of the samples. It is known to play a crucial role in the parasite invasion of the midgut of the mosquito [38]. A study has shown that its levels are elevated in infected red blood cells compared to uninfected cells.…”
Section: Discussionmentioning
confidence: 99%